Acute abdomen after hysterosalpingography-flare up of subclinical abdominal Kochs or endometriosis, a diagnostic dilemma - Shanbhag, Vijayalakshmi; Thakur, Pushpawati; Kashibhatla, Jyotsna; Agrawal, Sarita; Rajbhar, Sarita; Barman, Tithi (International Journal of Research in Medical Sciences, 2023)
Here we present the case report of a patient of infertility with endometriosis and undiagnosed underlying abdominal Kochs that exacerbated after hysterosalpingography (HSG), presenting as acute abdomen and causing a diagnostic dilemma. (HSG) is a diagnostic test used to evaluate the fallopian tubes and uterus. HSG is contraindicated in FGTB as it can result in flare-up of subclinical infection. However, it is often performed as part of infertility workup in unsuspected cases. In our patient the unsuspected preexisting abdominal Kochs got flared up after extravasation of the contrast material during HSG resulting in formation of pus and diffuse peritonitis. Explorative laparotomy was taken after 1 week of conservative management and pus drained along with ovarian cystectomy. The patient was started on antitubercular treatment postoperatively and recovered well.